A Review on Polyaniline: Synthesis, Properties, Nanocomposites, and Electrochemical Applications - Abdulwahhab H. Majeed; Leqaa A. Mohammed; Omar G. Hammoodi; Shankar Sehgal; Mustafa A. Alheety; Kuldeep K. Saxena; Safaa A. Dadoosh; Israa K. Mohammed; Mustafa M. Jasim; N. Ummal Salmaan (International Journal of Polymer Science)
The development in the use of polyaniline (PANI) in advanced studies makes us draw attention to the presented research and combine it into one study like this one. The unique composition of PANI qualifies it for use in electrochemical applications in addition to many other applications whose use depends on its mechanical properties. Based on this, it is necessary to limit the reactions that produce PANI and the cheapest cost, and then limit the current uses in the formation of nanocomposites with metals, their oxides, and/or carbon nanocomposites in order to determine what is missing from them and work on it again to expand its chemistry. The development in the use of PANI in advanced studies makes us draw attention to the research presented on PANI and combine it into one study. One of the very important things that made PANI possess a very huge research revolution are preparation in a variety of ways, easy and inexpensive, from which a daily product can be obtained with very high purity, as well as its distinctive properties that made it the focus of researchers in various scientific departments. The unique structure of PANI, which is easy to prepare in its pure form or with various chemical compounds including metals, metal oxides, and carbon nanomaterials (such as carbon nanotubes, graphene, graphene oxide, and reduced graphene oxide), qualifies it for use in electrochemical applications. The various studies reviewed showed that PANI gave good results in the applications of super capacitors. In some of the studies mentioned later, it gave a specific capacitance of 503 F/g, cycle stability 85% at 10,000 cycles, energy density 8.88 kW/kg, and power density 96 W h/kg. It was also noted that these values improved significantly when using PANI with its nanocomposites. Because of its good electrical conductivity and the possibility of preparing it with a high surface area with nanostructures in the form of nanowires, nanofibers, and nanotubes, PANI was used as a gas sensor. We have noticed, through the studies conducted in this field, that the properties of PANI as a basic material in gas sensors are greatly improved when it is prepared in the form of PANI nanocomposites, as explained in detail later. From this review, we tried with great effort to shed light on this attractive polymer in terms of its different preparation methods, its distinctive properties, its nanocomposites, and the type of polymerization used for each nanocomposites, as well as its applications in its pure form or with its nanocomposites in the supercapacitor and gas sensor applications.